Identity security through social capital networks in the UAE society: A sociological study on a sample of citizens from the Emirate of Sharjah - Al-Gharbawi, Fatima Ahmed; Al-Hourani, Mohammed; Al-Medani, Khalil (Al-Adab Journal, 2022)
The study sought to reveal the dimensions of identity security through social capital networks in the neighborhoods of the Emirate of Sharjah, and to achieve this, the dimensions of identity security and the strength of its presence in social capital networks were measured, by focusing on five components of identity security, which are "Homogeneous referential security, spatial mobility security, intellectual security, mobility security, and emotional security" The study sample included (421) males and females from the following neighborhoods of the Emirate of Sharjah: “Al-Wafjah, Al-Rahmaniya, Al-Zahiya, Central Region (Al-Dhaid), and from the eastern coast “Khorfakkan”. The results showed that social capital is a pillar of identity security, as it was found that the network of relationships in the neighborhoods of the Emirate of Sharjah that is limited to the presence of citizens is strong and is continuously reproduced, unlike mixed neighborhoods, and among the most prominent dimensions of identity security extended through the network of social relations in the neighborhoods inhabited by Emirati citizens: First: The security of the homogeneous reference, which is represented in “unity of appearance, customs and traditions, social responsibility, kinship relations.” Second: the security of mobility represented by “freedom of movement, lack of fear, and the security of public facilities in the neighborhood.” Third: intellectual security represented in “social harmony, Doctrinal coherence in the neighborhood". Fourth: The security emanating from rotational control represented in “social density, and security towards internal problems” such as theft and servants’ problems; Fifth: Emotional security represented by “trust, comfort, and emotional satisfaction” In addition to the existence of a statistically significant relationship between a number of primary variables “such as trust, participation, cooperation, and frequent meeting” and between the different dimensions of identity security. Identity security hubs vary according to the neighborhood and place of residence.